Job adjustment predictive factors of healthcare midwives in health system reform in Iran - Monireh Rezaee Moradali; Sepideh Hajian; Hamid Alavi Majd; Mohammadreza Rahbar; Rasool Entezarmahdi (BMC, 2023)
Abstract Background Possessing sensitive and multiple responsibilities in the country's health system, particularly after the implementation of the health reform in Iran, midwives must be able to optimally perform their duties in their new job as healthcare providers. This study aimed to identify the factors that predict job adjustment for Iranian midwives working in healthcare. Methods In this cross-sectional study, 310 midwives were recruited from 209 health centers in the Iranian province of West Azerbaijan using the census method and asked to complete research questionnaires. Data were collected using job adjustment, job satisfaction, and organizational commitment scales. SPSS version 25 was used to perform ANOVA and calculate multiple linear regression coefficients for data analysis. In addition, the AMOS software was employed for path analysis and the identification of predictive variables. Results The mean age of the participants was 37.67 ± 7.1 years. Most participants (35.5%) were interested in their occupation as a midwife, and 27.1% were very interest. They had a moderate to strong tendency (76.1%) to remain in their new profession. In addition, 58.1% of participants experienced moderate job adjustment. For healthcare midwives, "desire to remain in the midwifery profession" and "organizational commitment" were significant predictors of job adjustment. "Desire to remain in the midwifery profession" directly affected midwives' job adjustment, while "interest in the new profession" had an indirect effect. Furthermore, "adequacy of income to expenses," "job satisfaction," and "organizational commitment" through the mediating role of "desire to remain in the profession" can, directly and indirectly, influence their job adjustment. Conclusion To better prepare midwives for their role as healthcare providers, organizational managers should focus their efforts and plan primarily on providing incentives to increase the longevity of staying in the profession of midwifery increase job adjustment, job satisfaction, and organizational commitment, thereby improving the quality-of-service delivery.